Effectiveness of Medicine Ball Twist Toss Exercises Against Flick Drag Skills In Hockey Games - Syahruddin Syahruddin; Muhammad Syahrul Saleh; M. Sahib Saleh (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The drag flick technique is currently used by following the development of the synthetic field (carpet) with a more flat and slippery surface, so this technique can be used as a strategy to create goals. This study aims to determine the effect of medicine ball twist toss on drag flick skills in hockey games. This type of research is experimental with the treatment variable being medicine ball twist toss (MBT) exercise while the response variable is drag flick (DF) skill in hockey games. The sample was 20 people from the Hockey BKMF FIK UNM athletes, and they were divided into two groups, namely the experimental group (MBT training) and the control group (KK). The data collection technique used the shooting drag flick test instrument. Based on the results of the study, MBT training significantly improved DF skills in hockey (p<0.05). Therefore, improving DF skills can be done through MBT exercises.